2009
DOI: 10.1007/s11661-009-9926-x
|View full text |Cite
|
Sign up to set email alerts
|

Phenomenological Model for Deformation-Induced Ferrite Transformation

Abstract: A phenomenological model is proposed to describe the conditions under which an ultrafine ferrite (UFF) microstructure forms in low-alloyed steels as a result of deformation-induced ferrite transformation (DIFT). Assuming that corner points in the dislocation cell substructure of microshear bands provide suitable nucleation sites for ferrite, the model predicts that UFF forms in low-carbon steels independent of the steel chemistry and is promoted by increasing the strain rate. Analyzing ferrite growth rates sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…It is evident that immediate WQ after heavy deformation at 1073 K (800°C) (just above A r3 ) is able to retain the largest grain size below~6 lm in low-carbon steels, as shown in Figures 7(d), (l), and 8(c). This observation can be supported by the work of Beladi et al [21] and Huang et al [37] The average grain size of the 1073-0.9-1s-WQ sample (1.6 lm), which agrees well with the predicted DSIT-ferrite grain size, followed the work of Militzer and Brechet [38] for the true strain (0.9) and strain rate (10/s) used in present study. The average grain size of the 1073-0.9-1s-WQ sample can be used then as D a0 in the following equation, for the prediction of average a-grain size (D a ) in the 1073-0.9-100s-WQ sample, as a function of time (100 seconds) and temperature (1073 K [800°C]) of isothermal holding: [39] …”
Section: Ferrite Grain Refinement and Grain Size Distributionssupporting
confidence: 90%
See 1 more Smart Citation
“…It is evident that immediate WQ after heavy deformation at 1073 K (800°C) (just above A r3 ) is able to retain the largest grain size below~6 lm in low-carbon steels, as shown in Figures 7(d), (l), and 8(c). This observation can be supported by the work of Beladi et al [21] and Huang et al [37] The average grain size of the 1073-0.9-1s-WQ sample (1.6 lm), which agrees well with the predicted DSIT-ferrite grain size, followed the work of Militzer and Brechet [38] for the true strain (0.9) and strain rate (10/s) used in present study. The average grain size of the 1073-0.9-1s-WQ sample can be used then as D a0 in the following equation, for the prediction of average a-grain size (D a ) in the 1073-0.9-100s-WQ sample, as a function of time (100 seconds) and temperature (1073 K [800°C]) of isothermal holding: [39] …”
Section: Ferrite Grain Refinement and Grain Size Distributionssupporting
confidence: 90%
“…Overall, the average a-grain sizes of the specimens, where DSIT is expected to happen in the present study (Table II), are similar to the range of values (2.1 to 3.0 lm) reported earlier for the plain C-Mn or microalloyed steel specimens, air-cooled or slowly cooled after heavy deformation, around A r3 . [21,30] Zhang et al [24] and Militzer and Brechet [38] carried out initial modeling studies for the prediction of fraction and size of DSIT ferrite grains, as the function of (average) initial c-grain size, e, _ e, and T def . However, it should be remembered that DSIT is not synonymous with the development of UFF grain structure.…”
Section: Dynamic Recovery and Recrystallization Of Ferritementioning
confidence: 99%
“…The value of K1 is assumed to be the same as that reported by Umemoto et al 27) The area of the austenite grain boundary, Sgb, is calculated from the length of the austenite grain boundary, lg, which, in turn, is calculated through the MPF simulation as follows: On the other hand, in order to describe the evolution of the density of the activated ferrite nucleation sites on the microshear band, we determine using the following equation: 28) .............. (21) where ε0 is the critical strain for the initiation of microshear band formation and is a parameter representing the strain-rate sensitivity of the microshear band formation process. Here, and εref are the applied strain rate and the referential strain rate, respectively.…”
Section: Nucleation Of Ferrite Grains During Dift Andmentioning
confidence: 99%
“…In order to determine the input parameters for the MPF model, we performed a preliminary simulation of the DIFT in a Fe-0.15wt.%C alloy at a temperature of 750°C and strain rate of 0.1 s -1 ; these conditions are same as those employed by Choi et al 32) Then, the parameters to be used for the subsequent MPF simulation were identified by comparing the simulated flow stress curve with the experimentally determined one. The physical values and input parameters obtained using the above-mentioned procedure are shown as follows: [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] For Eqs. (3) and (4) .…”
Section: Simulation Condition and Proceduresmentioning
confidence: 99%
“…[20,21] The main laws used correspond to Avrami and Voce, and the Garofalo equation is only used to supply some of the necessary parameters. [22,23] Another approximation for the construction of the constitutive equation extended for a large range of strains is based on dimensional analysis of various variables that are of physical significance such as the stacking fault energy, grain size, dislocation density, etc. [24] This model needs a large amount of microstructural data and works with a large amount of variables.…”
Section: ( ) ( )mentioning
confidence: 99%